Endoplasmic reticulum stress and unfolded protein response in immune cell function - Matsushima, Goshi; Yanase, Yuhki; Nakagawa, Tadashi; Goda, Mitsuhiro; Ozawa, Koichiro; Hosoi, Toru (Frontiers in Immunology, 2025)
Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) have emerged as central regulators of immune cell function and inflammatory processes. The UPR, mediated by three principal ER-resident sensors, IRE1α, PERK and ATF6, maintains cellular homeostasis under stress conditions but also contributes to pathogenesis when dysregulated. Recent studies revealed that the UPR plays critical roles not only in protein folding but also in directing immune cell fate, activation, and cytokine production. Although significant advances have been made, various questions remain regarding the cell-type-specific and context-dependent functions of ER stress responses. Understanding these mechanisms would be crucial for developing targeted therapies. Therefore, in this review, we provide a comprehensive overview of how ER stress and the UPR influence various immune cell types, including monocytes, macrophages, dendritic cells, granulocytes, T cells, B cells, microglia, and astrocytes, within both peripheral and central immune systems.